Association between Helicobacter pylori infection, mismatch repair, HER2 and tumor-infiltrating lymphocytes in gastric cancer - Castaneda, CA (2024)
BACKGROUND The influence of Helicobacter-pylori (H. pylori) infection and the characteristics of gastric cancer (GC) on tumor-infiltrating lymphocyte (TIL) levels has not been extensively studied. Analysis of infiltrating-immune-cell subtypes as well as survival is necessary to obtain comprehensive information. AIM To determine the rates of deficient mismatch-repair (dMMR), HER2-status and H. pylori infection and their association with TIL levels in GC. METHODS Samples from 503 resected GC tumors were included and TIL levels were evaluated following the international-TILs-working-group recommendations with assessment of the intratumoral (IT), stromal (ST) and invasive-border (IB) compartments. The density of CD3, CD8 and CD163 immune cells, and dMMR and HER2-status were determined by immunohistochemistry (IHC). H. pylori infection was evaluated by routine histology and quantitative PCR (qPCR) in a subset of samples. RESULTS dMMR was found in 34.4%, HER2+ in 5% and H. pylori-positive in 55.7% of samples. High IT-TIL was associated with grade-3 (P = 0.038), while ST-TIL with grade-1 (P < 0.001), intestinal-histology (P < 0.001) and no-recurrence (P = 0.003). dMMR was associated with high TIL levels in the ST (P = 0.019) and IB (P = 0.01) compartments, and STCD3 (P = 0.049) and ST-CD8 (P = 0.05) densities. HER2-was associated with high IT-CD8 (P = 0.009). H. pylorinegative was associated with high IT-TIL levels (P = 0.009) when assessed by routine-histology, and with high TIL levels in the 3 compartments (P = 0.002-0.047) and CD8 density in the IT and ST compartments (P = 0.001) when assessed by qPCR. A longer overall survival was associated with low IT-CD163 (P = 0.003) and CD8/CD3 (P = 0.001 in IT and P = 0.002 in ST) and high IT-CD3 (P = 0.021), ST-CD3 (P = 0.003) and CD3/CD163 (P = 0.002). CONCLUSION TIL levels were related to dMMR and H. pylori-negativity. Low CD8/CD3 and high CD163/CD3 were associated with lower recurrence and longer survival.